Assessment of metal variations in water, sediment, and fish species (Pangasius sp. and Hemibagrus sp.) from Selangor River, Pahang River and nearby aquaculture ponds / Nor Shahirul Umirah Idris - Nor Shahirul Umirah , Idris (2018)
This study aims to evaluate the spatial distributions of metal elements in water, sediments, and fish species (Pangasius sp. and Hemibagrus sp.) sampled from Selangor River, Pahang River and nearby aquaculture ponds, and to assess the safety of the fish consumption. The concentrations of Na, Mg, K, Ca, Cr, Fe, Ni, Cu, Zn, As, Se, Cd, and Pb in those samples were determined using the microwave-assisted digestion-inductively coupled plasma-mass spectrometric method which has been verified with a series of certified reference materials. The natural clustering tendency corresponding to metal variability was explored using principal component analysis and hierarchical cluster analysis. The results revealed that the metal variability in the waterbody and sediment samples mostly originated from human activities around the sampling sites, in addition to natural variations. Such variations were also reflected on the metal accumulation pattern in the sampled fish, although the variations between different tissues were mainly subjected to their metabolic activities. Based on the findings, Hemibagrus sp. was suggested as a potential bioindicator for hazardous metal pollution. In risk and safety assessment, the metal concentrations in the edible muscle of the fish samples were found to be below the established limits, although target hazard quotient of As and Se in wild Hemibagrus sp. from Selangor River approached unity.